The representation of patient experience and satisfaction in physician rating sites. A criteria-based analysis of English- and German-language sites - Strech Daniel; Reimann Swantje (BMC, 2010)
Abstract Background Information on patient experience and satisfaction with individual physicians could play an important role for performance measures, improved health care and health literacy. Physician rating sites (PRSs) bear the potential to be a widely available source for this kind of information. However, patient experience and satisfaction are complex constructs operationalized by multiple dimensions. The way in which PRSs allow users to express and rate patient experience and satisfaction could likely influence the image of doctors in society and the self-understanding of both doctors and patients. This study examines the extent to which PRSs currently represent the constructs of patient experience and satisfaction. Methods First, a systematic review of research instruments for measuring patient experience and satisfaction was conducted. The content of these instruments was analyzed qualitatively to create a comprehensive set of dimensions for patient experience and patient satisfaction. Second, PRSs were searched for systematically in English-language and German-language search engines of Google and Yahoo. Finally, we classified every structured question asked by the different PRS using the set of dimensions of patient experience and satisfaction. Results The qualitative content analysis of the measurement instruments produced 13 dimensions of patient experience and satisfaction. We identified a total of 21 PRSs. No PRSs represented all 13 dimensions of patient satisfaction and experience with its structured questions. The 3 most trafficked English-language PRS represent between 5 and 6 dimensions and the 3 most trafficked German language PRSs between 8 and 11 dimensions The dimensions for patient experience and satisfaction most frequently represented in PRSs included diversely operationalized ones such as professional competence and doctor-patient relationship/support. However, other less complex but nevertheless important dimensions such as communication skills and information/advice were rarely represented, especially in English-language PRSs. Conclusions Concerning the potential impact of PRSs on health systems, further research is needed to show which of the current operationalizations of patient experience and satisfaction presented in our study are establishing themselves in PRSs. Independently of this factual development, the question also arises whether and to what extent health policy can and should influence the operationalization of patient experience and satisfaction in PRSs. Here, the challenge would be to produce a set of dimensions capable of consensus from among the wide range of operationalizations found by this study.